Government agencies and their discourses of flood disaster preparedness : impact on response, action and community empowerment - Sandaran S.C.,; Selvaraj S., (Penerbit Universiti Kebangsaan Malaysia, 2021)
One of the severe global threats facing the world today is flooding. Similarly, Malaysia is faced with monsoon and flash floods which are the most severe "climate-related natural disasters" for the country. The Malaysian government is the main stakeholder and provider of aid in every stage of disaster. Consequently, the involvement of flood risk communities is said to be minimal and overlooked. Researchers have also stated that there is still a lack of research on human involvement and response. Thus, addressing these gaps, we take on a social constructionist view to situate flood disaster as a social practice and discourse to investigate how government officials ‘talk’ about their involvement in flood disaster mitigation and management. Our analysis is based on the perspective that their ‘talk’ evokes specific disaster discourses which relate to the different ways of understanding flood disaster, and that these discourses in turn shape and impact their response and action for flood mitigation and management as well as community empowerment. To this end, we adopt Van Leeuwen’s representation of social actors and social action framework to identify the disaster discourses drawn upon by the officials. The findings show that government officials employ various discourses that draw on the ‘traditional framework of relief and rehabilitation’ and a ‘top-down government centric approach’ that focus less on community empowerment. We see a need for the inclusion of a ‘discourse of shared responsibility’ that is part of a ‘proactive approach’, and sees all parties as partners, and in particular, flood risk communities.